MIDWIFE, COUNSELING AND ADOLESCENT REPRODUCTIVE HEALTH RIGHTS IN COVID-19 PANDEMIC - Sumiari, Karlina; Lufiana, Indrie; Prima, Dian (Rena Cipta Mandiri, 2022)
Cases related to adolescent health have increased during the COVID-19 pandemic. Midwives have a very important role in conducting counseling related to adolescent health. This is a form of commitment in fulfilling the right to health of adolescents. The role of the midwife is stated in terms of reproductive health in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 28 of 2017 concerning Permits and Implementation of Midwifery Practices article 21a. The purpose of this research is to know the role of midwives in the implementation of adolescent counseling as the fulfillment of adolescent reproductive health rights. Qualitative research methods, with a sociological juridical approach. The study used in-depth interviews with midwife and adolescent informants. The research was conducted from May to June 2021. Data analysis was carried out by qualitative data analysis. The results of the study show that BIdans have carried out their authority and obligations in the role of counselors based on the Midwifery Law Number 4 of 2019 and the Regulation of the Minister of Health of the Republic of Indonesia Number 28 of 2017 concerning Permits and Implementation of Midwifery Practices article 21a. The role of midwives in the implementation of adolescent counseling is to increase knowledge of reproductive health as a fulfillment of adolescent reproductive health rights. Midwives are implementers of youth health service programs. Reproductive health rights in adolescents based on the International Conference on Population and Development (ICPD) in Cairo in 1994 there are 12 rights of which 11 reproductive health rights have been well fulfilled.